(untitled) (La U Investiga, 2021)
The Kolcaba’s theoretical precepts reaffirm that the approach to comfort interventions is not usually only technical, they complement clinical care and help to satisfy the basic human needs of the patient. In this sense, the nursing discipline has a relevant role. The objective of this study was to categorize the dimensions of comfort focused on Kolcaba’s theory in hospitalized patients. Design of a quantitative approach, with a descriptive and transversal scope. The sample was made up of 86 patients from the Internal Medicine area of the San Vicente de Paúl Hospital, the instrument called S-GCQ General Comfort Questionnaire Spanish, designed by Kolcaba, was applied. In relation to the physical dimension, it was observed that the patients have difficulty withstanding pain and lack family support to walk.In the psychospiritual dimension, faith and beliefs promote a state of peace and tranquility in the patient. The lack of time and training on the part of the professionals prevents executing the interventions that are required in this dimension. In the environmental dimension, patients do not have enough privacy due to the lack of screens or curtains in each cubicle. The nursing professional must support the care in the precepts enunciated by Kolcaba to provide holistic care to the patient.